Pengaruh Penerapan Slow Deep Breathing Terhadap Keletihan (Fatigue) Pada Pasien Penyakit Ginjal Kronik Yang Menjalani Hemodialisis Di Rsud Koja - Afrilia Eka Putri; Imam Subiyanto; Riza Ginanjar Mustofa (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Chronic kidney disease (CKD) is a systemic disease that is the final stage of various diseases related to the urinary tract and kidneys. The prevalence of chronic kidney failure exceeds 10% of the general population worldwide, with a total of approximately 843.6 million sufferers. Hemodialysis brings many benefits to patients, but hemodialysis also has side effects such as fatigue, hypotension, nausea and vomiting, muscle cramps, and sleep disorders. Undergoing hemodialysis therapy by applying slow deep breathing. This study used a quantitative pre-experimental design with a pre-test-post-test one group design approach. Data collection was conducted on December 10-12, 2025, with a sample of 30 using inclusion and exclusion criteria. The majority of those undergoing hemodialysis were men (56.7%) with age 40-59 years (73.3%). Duration of hemodialysis >2 years (63.3%), frequency 2x a week (100%), duration 4 hours (60.0%). The fatigue levels obtained were moderate (56.7%) and severe (43.3%). The Wilcoxon Rank-Test obtained a p-value of <0.000. There is an effect of slow deep breathing on fatigue in chronic kidney failure patients undergoing hemodialysis at Koja Regional Hospital. Recommendation: It is hoped that they can do deep breathing independently at home when feeling tired.